Clinical Applications of PCR - Lo, Y. M. Dennis; Chiu, Rossa W. K.; Chan, K. C. Allen; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2006)
In this updated second edition of the much praised Clinical Applications of PCR, leading researchers apply molecular diagnostics to the many recent advances that have occurred in polymerase chain reaction (PCR)-based technologies. Highlights include real-time PCR, which allows the technique to be performed in a quantitative manner with improved sensitivity, robustness, and resilience to carryover contamination, mass spectrometric analysis of nucleic acids, and circulating cell-free nucleic acids in plasma. The authors apply these innovations to a broad spectrum of applications, including gene expression, methylation, trace molecule, gene dosage, and single cell analysis. The protocols follow the successful Methods in Molecular Biology$1!" (Bseries format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. State-of-the-art and highly practical, Clinical Applications of PCR, Second Edition, will help today's laboratorians and researchers working in molecular diagnostics harness the power of these techniques with unprecedented sensitivity and ease.s
to the Polymerase Chain Reaction -- Setting Up a Polymerase Chain Reaction Laboratory -- Real-Time Polymerase Chain Reaction and Melting Curve Analysis -- Qualitative and Quantitative Polymerase Chain Reaction-Based Methods for DNA Methylation Analyses -- In-Cell Polymerase Chain Reaction -- Qualitative and Quantitative DNA and RNA Analysis by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry -- Analysis of Polymerase Chain Reaction Products by Denaturing High-Performance Liquid Chromatography -- Use of Real-Time Polymerase Chain Reaction for the Detection of Fetal Aneuploidies -- Noninvasive Prenatal Diagnosis by Analysis of Fetal DNA in Maternal Plasma -- Clinical Applications of Plasma Epstein-Barr Virus DNA Analysis and Protocols for the Quantitative Analysis of the Size of Circulating Epstein-Barr Virus DNA -- Molecular Analysis of Circulating RNA in Plasma -- Molecular Analysis of Mitochondrial DNA Point Mutations by Polymerase Chain Reaction -- Novel Applications of Polymerase Chain Reaction to Urinary Nucleic Acid Analysis -- Detection and Quantitation of Circulating Plasmodium falciparum DNA by Polymerase Chain Reaction -- Molecular Diagnosis of Severe Acute Respiratory Syndrome -- Genomic Sequencing of the Severe Acute Respiratory Syndrome-Coronavirus.
Keywords: Life sciences; Cell biology; Life Sciences; Cell Biology; Electronic books